STUDENTS' LEARNING DIFFICULTIES AND THEIR HANDLING IN CLASS IV SCIENCE LEARNING IN STATE PRIMARY SCHOOL 16 BANDA ACEH - Putri Lara Maulida; Siti Mayang Sari (Sensei International Journal of Education and Linguistic, 2024)
The aim of this research is to determine students' learning difficulties and their responses to class IV science learning at SDN 16 Banda Aceh. This research uses qualitative research methods with a qualitative descriptive design. This research was carried out on the basis of a phenomenon that occurred in one case at SDN 16 Banda Aceh. Researchers found Based on the results of data analysis, the results obtained are; a) The types of mathematics learning difficulties experienced by elementary/MI students are divided into two, namely difficulties that originate from within the student and those that originate from outside the student, and how to handle them, namely; 1) Carrying out a diagnosis of learning difficulties in students, 2) Providing remedial learning guidance for science learning and 3) Implementing the Personal Resilience Curriculum, and Using Blended Learning. b) Factors that cause elementary/MI students' learning difficulties are factors that originate from within the student (internal) and factors that originate from outside the student (external). Data was collected through observation, interviews and documentation.